Analysis of The Influence of Digitalization of The Book Industry on The Performance of Traditional Traders - Muhammad Aras Prabowo; Muchtar Ahmad Yasin; Sintia Nur Afifah; Nur Ain Ayunni Sabri (Trescode Green Organization, 2025)
The advancement of digital technology has caused a significant shift in the book industry, altering the way consumers access and purchase literature. This study explores the impact of book digitalization on the performance of traditional book vendors in Indonesia. Digitalization, encompassing e-books and digital distribution platforms, offers convenience and lower costs, leading to a decline in the demand for physical books and challenging traditional business models. This research employs a qualitative approach with a literature review methodology. Data were collected from relevant literature, industry reports, and previous studies to analyze the changing trends in the book industry and their effects on traditional vendors. Descriptive analysis is used to interpret how digitalization impacts the demand for physical books and the adaptation strategies employed by book vendors. The findings reveal that book digitalization has led to a significant decline in the sales of physical books at traditional bookstores. Consumers now prefer the convenience and lower cost of digital books, resulting in reduced revenue and operational challenges for physical book vendors. While digitalization offers efficient solutions for book distribution and procurement, it also requires traditional vendors to adapt. The implications of this study highlight the need for traditional book vendors to adopt digital strategies, such as developing e-commerce platforms and integrating technology, to maintain their relevance in the evolving market. The study suggests that book vendors explore product and service diversification to meet the needs of increasingly digital consumers and invest in innovation to remain competitive in the digital age.